Hubungan antara lama menjalani hemodialisis dengan kualitas hidup pasien yang menjalani hemodialisis di Unit Hemodialisis RSUP. Prof. Dr. R. D. Kandou Manado - Rahman, Moch. T. S. A.; Kaunang, Theresia M. D.; Elim, Christofel (Universitas Sam Ratulangi, 2016)
Abstract: Chronic kidney disease (CKD) results in a decrease in kidney function that is irreversible and requires treatment in the form of a kidney transplant or hemodialysis. The main goal of hemodialysis is to prevent and control uremia, fluid overload, and electrolyte imbalance. Problems that commonly associate hemodialysis patients are physical and psycological stress that affect the quality of life. This study aimed to obtain the relationship between the duration of hemodialyis and the quality of life. This was an observational analytical study with a cross sectional design. The study included all hemodialysis patients in Dahlia and Melati Hemodialysis Unit Prof. Dr. R. D. Kandou Hospital Manado. There were 34 patients that met the inclusion criteria. The results showed that the correlation between the duration of hemodialyis and the quality of life had a p value of 0.579. Conclusion: The duration of hemodialysis did not correlate significantly with the quality of life of hemodialysis patients.Keywords: The duration of hemodialysis, quality of life.Abstrak: Gagal ginjal kronik (PJK) mengakibatkan penurunan fungsi ginjal yang ireversibel, yang memerlukan terapi berupa transplantasi ginjal atau hemodialisis. Tujuan utama hemodialisis yaitu mengendalikan uremia, kelebihan cairan dan ketidakseimbangan elektrolit. Permasalahan yang muncul pada pasien hemodialisis ialah masalah fisik, psikologi, perubahan sosial, dan gaya hidup; hal tersebut memengaruhi kualitas hidup pasien. Peneltian ini bertujuan untuk mencari hubungan antara lama menjalani hemodialisis dengan kualitas hidup. Metode penelitian yang digunakan ialah observasional analitik dengan pendekatan potong lintang Penelitian ini melibatkan semua pasien hemodialisis di Unit Hemodialisis Dahlia dan Melati RSUP Prof. Dr. R. D. Kandou Manado yang memenuhi kriteria inklusi yaitu sebanyak 34 orang. Hasil penelitian menunjukkan korelasi antara lama menjalani hemodialisis dengan kualitas hidup dengan nilai P=0,579. Simpulan: Tidak terdapat hubungan antara lama menjalani hemodialisis dengan kualitas hidup pada pasien hemodialisis.Kata kunci: lama menjalani hemodialisis, kualitas hidup.